2012
DOI: 10.1016/j.bbadis.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Sex, rebellion and decadence: The scandalous evolutionary history of the human Y chromosome

Abstract: It can be argued that the Y chromosome brings some of the spirit of rock&roll to our genome. Equal parts degenerate and sex-driven, the Y has boldly rebelled against sexual recombination, one of the sacred pillars of evolution. In evolutionary terms this chromosome also seems to have adopted another of rock&roll's mottos: living fast. Yet, it appears to have refused to die young. In this manuscript the Y chromosome will be analyzed from the intersection between structural, evolutionary and functional biology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…In addition, the importance of this histone demethylase in fertility may even extend to humans. For several decades we and others have observed that deletions of the AZFb (AZoospermia Factor b) region of the human Y chromosome are causative agents of male infertility due to a complete block of sperm meiotic maturation 50 51 52 . The 6.2 Mb-long AZFb deletions can affect up to 10 different genes and, therefore, the molecular mechanism(s) responsible for the infertility phenotype remain(s) unknown 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the importance of this histone demethylase in fertility may even extend to humans. For several decades we and others have observed that deletions of the AZFb (AZoospermia Factor b) region of the human Y chromosome are causative agents of male infertility due to a complete block of sperm meiotic maturation 50 51 52 . The 6.2 Mb-long AZFb deletions can affect up to 10 different genes and, therefore, the molecular mechanism(s) responsible for the infertility phenotype remain(s) unknown 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the autosomal chromosomes, which undergo recombination during meiosis, the Y chromosome does not recombine and has had to evolve its own method of maintaining the fidelity of its genetic material. The Y chromosome undergoes homologous arm‐to‐arm recombination of 8 massive palindromic sequences (Skaletsky et al ., ; Lange et al ., ) Because of the fact that it has only one copy of its critical genetic material, any deletion or mutation of this material may have a severe impact on a man's spermatogenesis potential (Simoni et al ., ,b; Navarro‐Costa, ). If ectopic homologous recombination occurs and there is a deviation from the standard intra‐palindromic arm‐to‐arm recombination, a man may lose some of the material crucial to normal spermatogenesis.…”
Section: Chromosomal Translocationsmentioning
confidence: 99%
“…First, males and females differ substantially regarding their respective human sex chromosome composition. 22 Whereas the X chromosome has 836 active protein-coding genes, the Y chromosome has 52 active genes (of which 25 are specific to males only, whereas 27 genes are in the Y chromosome' s pseudoautosomal region and are also found on the X chromosome). Because most X chromosome genes are present in only 1 copy in males, the risk of recessive disease vulnerability is increased.…”
Section: Figurementioning
confidence: 99%